Atomically precise copper nanoclusters as ultrasmall molecular aggregates: Appealing compositions, structures, properties, and applications. Issue 1 (13th September 2022) - Zhang, Leon Li‐Min; Wong, Wai‐Yeung
Abstract: Metal nanoclusters (NCs) are ultrasmall molecular aggregates consisting of dozens to hundreds of metal atoms consolidated by organic ligands, which represent an emerging area of nanoscience. Amide a myriad of metal NCs, copper NCs (CuNCs) comprise a low‐cost, high‐value subclass that has attracted great attention. The variable copper cores and diversity of protecting ligands have rendered CuNCs interesting molecular aggregates featuring structural and compositional versatility, hence showing distinctive properties and potential applications. In the present review, we have summarized the progress on atomically precise CuNCs that exhibit a range of appealing properties and applications in different fields. This review is expected to provide not only an overview of the current development on atomically precise CuNCs, but also possible directions for the future design of novel CuNCs for fundamental studies and practical applications. Abstract : In the present review, we provide an overview on copper nanoclusters (CuNCs) that exhibit atomically precise compositions and structures to simultaneously show functional properties and applications. This review not only offers an understanding of CuNCs as an emerging class of molecular aggregates, but also provides guidelines for future exploration of their novel properties and practical applications.